2022
DOI: 10.1136/ard-2022-222849
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab in enthesitis-related arthritis and juvenile psoriatic arthritis: a randomised, double-blind, placebo-controlled, treatment withdrawal, phase 3 trial

Abstract: BackgroundTreatment options in patients with enthesitis-related arthritis (ERA) and juvenile psoriatic arthritis (JPsA) are currently limited. This trial aimed to demonstrate the efficacy and safety of secukinumab in patients with active ERA and JPsA with inadequate response to conventional therapy.MethodsIn this randomised, double-blind, placebo-controlled, treatment-withdrawal, phase 3 trial, biologic-naïve patients (aged 2 to <18 years) with active disease were treated with open-label subcutaneous secuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…Currently, results of phase 3 clinical trials with secukinumab in the juvenile idiopathic arthritis including juvenile psoriatic arthritis patients were published, showing significantly longer time to disease flare when compared with placebo-treated patients. 64 Majority of the site effects were similar to those observed in adult patients treatment, with nasopharyngitis, nausea, upper respiratory tract infections, oropharyngeal pain, headache, fever and diarrhea being the most common ones. In one patient Crohn’s disease was diagnosed during the study.…”
Section: Psoriasis and Pediatric Psoriasis - Introductionsupporting
confidence: 53%
“…Currently, results of phase 3 clinical trials with secukinumab in the juvenile idiopathic arthritis including juvenile psoriatic arthritis patients were published, showing significantly longer time to disease flare when compared with placebo-treated patients. 64 Majority of the site effects were similar to those observed in adult patients treatment, with nasopharyngitis, nausea, upper respiratory tract infections, oropharyngeal pain, headache, fever and diarrhea being the most common ones. In one patient Crohn’s disease was diagnosed during the study.…”
Section: Psoriasis and Pediatric Psoriasis - Introductionsupporting
confidence: 53%
“…In a retrospective study that analyzed patients who had already been treated using biologics with other mechanisms of action, it was found that patients with JIA showed significant improvements in signs and symptoms in different disease domains [123]. In a recent phase-three study [124], the administration of this biologic was shown to reduce the frequency of disease flare-ups in children with JIA compared with control subjects. In more detail, the 2-year, randomized-withdrawal, double-blind, placebo-controlled JUNIPERA trial included 86 patients and consisted of three treatment periods.…”
Section: The Role Of Anti-il-17a Blocking Antibodies In Jpsa and Era ...mentioning
confidence: 99%
“…In the second period, responders received secukinumab or placebo. Secukinumab demonstrated a significantly longer time to disease flare and a consistent safety profile similar to adults (170). Moreover, there are ongoing clinical trials for ixekizumab (NCT04527380).…”
Section: Treatment and Outcomementioning
confidence: 90%